2015
DOI: 10.1016/j.ecohyd.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

A simple model to quantify the potential trade-off between water level management for ecological benefit and flood risk

Abstract: Article (refereed) -postprint Stratford, Charlie; Brewin, Phil; Acreman, Mike; Mountford, Owen. 2015. A simple model to quantify the potential trade-off between water level management for ecological benefit and flood risk.Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.A simple model to quantify the potential trade-off b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Within this context, a spatio‐temporal monitoring of natural habitats over hundreds of km 2 is needed to meet reporting requirements for the conservation status of European NATURA 2000 sites. To meet this requirement, natural habitats should be identified at the plant community level in order to assess the heritage quality (Berg et al., ), ecosystem services (Lavorel et al., ) and impacts of agricultural practices or water level management on vegetal biodiversity (Dumont et al., ; Stratford, Brewin, Acreman, & Mountford, ).…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, a spatio‐temporal monitoring of natural habitats over hundreds of km 2 is needed to meet reporting requirements for the conservation status of European NATURA 2000 sites. To meet this requirement, natural habitats should be identified at the plant community level in order to assess the heritage quality (Berg et al., ), ecosystem services (Lavorel et al., ) and impacts of agricultural practices or water level management on vegetal biodiversity (Dumont et al., ; Stratford, Brewin, Acreman, & Mountford, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results highlighted the critical influence of hydrology (water depth and duration of the drying events) on Odonata assemblages in agricultural marshland landscapes crossed by ditches. This suggests that ditch water management offers clear possibilities to maintain and possibly promote Odonata diversity (see also Herzon & Helenius, 2008;Stratford et al, 2015). For example, water management can be better designed to prevent drying episodes and hence to meet conservation purposes in anthropogenic aquatic systems (Bogan et al, 2020;Mauchamp et al, 2021;Twisk et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Research funded by SDBC helped to lessen this Conflict. Stratford et al (2015) demonstrated that RSPB direct and indirect management of the floodplain only marginally reduced floodplain storage and therefore was not a significant contributor to the 2013/14 floods. Research is likely to also play a role in scaling-up sFRM for instance on the effectiveness/opportunity/acceptability of NBS measures (Dadson et al, 2017;Broadmeadow et al, 2015;Holstead et al, 2014).…”
Section: Floodplain Connectivitymentioning
confidence: 96%